Neuroprotective Profile of Edible Flowers of Borage (Borago officinalis L.) in Two Different Models: Caenorhabditis elegans and Neuro-2a Cells - Cristina Moliner; Guillermo Cásedas; Lillian Barros; Tiane C. Finimundy; Carlota Gómez-Rincón; Víctor López (MDPI AG, 2022)
The flowers of Borago officinalis L. (Boraginaceae), commonly known as borage, are widely used as a culinary ingredient. The aim of this study was to assess the potential benefits of fresh borage flower extract related to antioxidant, neuroprotective and anti-aging properties. The extract was obtained by Soxhlet extraction with ethanol as a solvent, and fatty acids were detected by GC-FID. The antioxidant activity was evaluated in vitro through the DPPH, FRAP and ORAC assays. Regarding the fatty acid (FA) composition, the extract showed high amounts of polyunsaturated FA. The Neuro-2a cell line was used to determine the cytoprotective capacity of the extract subjected to oxidative stress (H2O2). Moreover, the model organism Caenorhabditis elegans was used to assess antioxidant activity, delayed ageing as well as cytoprotection and reduced β-amyloid toxicity. Cells treated with the extract and H2O2 showed a better response to oxidative stress than the control group, particularly in terms of mitochondrial activity (MTT assay), redox state (ROS formation) and the activity of antioxidant enzymes (catalase and superoxide dismutase). B. officinalis flower extract showed promising antioxidant activity in the selected models, without causing toxicity. Hence, the results obtained support the antioxidant properties of borage flowers in different bioassays using living organisms.